Development and psychometric testing of an instrument to compare career choice influences and perceptions of nursing among healthcare students - Liaw, Sok Ying (BMC Med Educ, 2017)
BACKGROUND: With the availability of more healthcare courses and an increased intake of nursing students, education institutions are facing challenges to attract school leavers to enter nursing courses. The comparison of career choice influences and perception of nursing among healthcare students can provide information for recruitment strategies. An instrument to compare the influences of healthcare career choice is lacking. The purpose of this study is to develop and evaluate the psychometric properties of an instrument to compare the influences of healthcare career choice with perceptions of nursing as a career choice. METHODS: The study was conducted in two phases. In phase one, two sets of scales with parallel items that measure the influences of healthcare career choice and perceptions of nursing as a career choice were developed through an earlier qualitative study, literature review, and expert validation. Phase two involved testing the construct validity, concurrent validity and reliability with a convenience sample of 283 first year healthcare students who were recruited at two education institutions in Singapore. RESULTS: An exploratory factor analysis revealed 35-parallel items in a six-factor solution (personal interest, prior healthcare exposure, self-efficacy, perceived nature of work, job prospects, and social influences) that explained 59 and 64% of the variance for healthcare career choice and nursing as a career choice respectively. A high correlation (r = 0.76, p < 0.001) was obtained with an existing tool, confirming the concurrent validity. The internal consistency was sufficient with Cronbach’s alpha of 0.93 for healthcare career choice and 0.94 for nursing as a career choice. The test-retest reliability was acceptable with an Intraclass Correlation Coefficient of 0.63 for healthcare career choice and 0.60 for nursing as a career choice. CONCLUSIONS: The instrument provides opportunities for understanding the differences between influences of healthcare career choice and perceptions of nursing as a career choice. This comparative understanding of career choice influences can guide educator and policy-makers on nursing recruitment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-017-0910-7) contains supplementary material, which is available to authorized users.